Practice and Evaluation of a Protocol for Collating Information Related to the Emergency Clinical Pathway for Patients With Acute ST-Segment Elevation Myocardial Infarction - Cao, Jun; Ge, Zi; Zhao, Hui; Ma, Ke; Xia, Zhijie (Frontiers in Cardiovascular Medicine, 2022)
Acute ST elevation myocardial infarction (STEMI) is a common acute and critical disease that requires rapid treatment within a limited window of time. In this study, we attempt to introduce a clinical pathway for the whole-process management of emergency STEMI based on the creation of a specific information system that matches the characteristics of emergency clinical work and evaluates their clinical value by quality control analysis. We deployed this system for three years and found that complications, heart failure, and medical costs during hospitalization were significantly reduced (p=0.019) in patients with STEMI. By analyzing each link in the clinical pathway, our research indicates the clear clinical importance of developing methods to continuously improve data quality. Collectively, out research led to the optimization of an information system that will facilitate the clinical management of patients with STEMI.